Clitocybula sulcata—a new species from India - Latha, K. P. Deepna; Raj, K. N. Anil; Sharafudheen, Shahina A.; Manimohan, Patinjareveettil (Phytotaxa, 2015)
Clitocybula sulcata sp. nov. is described from Kerala State, India. This species is characterized by a distinctly sulcate, finely granulose pileal surface, and a possible association with the bark of living Hydnocarpus (Flacourtiaceae) trees. A comprehensive description, photographs, and comparisons with phenetically similar species are provided. Molecular phylogenetic analyses based on ITS sequences coupled with morphology confirmed the placement of this species in Clitocybula. The present study is the first description of a species of this genus from India.